Dynamic response analysis of induction motor drive influenced by controller design methods - Kaewma, Panuwat; Pothi, Nattapong; Rakpenthai, Chawasak (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper proposes a comparison study focusing on the dynamic response and tracking accuracy for the induction motor drive system influenced by the controller design methods. Pole-zero cancellation (PZC) and pole placement (PP) methods are commonly used to define the controller gains for motor drive systems, and both methods are verified in this paper. The bandwidth of controllers for both methods is set equally based on the field-oriented control strategy, which consists of current and speed control loops. Furthermore, the test conditions are defined to examine the drive system performance, i.e., i) load torque rapidly changes with the maintained speed and ii) speed changes in no-load and with-load torque conditions to validate the current and speed control loops, respectively. The validation of the drive system performance influenced by the controller design methods is demonstrated by simulation results.